1995
DOI: 10.1128/jb.177.1.200-205.1995
|View full text |Cite
|
Sign up to set email alerts
|

Inositol monophosphatase activity from the Escherichia coli suhB gene product

Abstract: The suhB gene is located at 55 min on the Escherichia coli chromosome and encodes a protein of 268 amino acids. Mutant alleles of suhB have been isolated as extragenic suppressors for the protein secretion mutation (secY24), the heat shock response mutation (rpoH15), and the DNA synthesis mutation (dnaB121) (K. Shiba, K. Ito, and T. Yura, J. Bacteriol. 160:696-701, 1984; R. Yano, H. Nagai, K. Shiba, and T. Yura, J. Bacteriol. 172:2124-2130, 1990; S. Chang, D. Ng, L. Baird, and C. Georgopoulos, J. Biol. Chem. 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 43 publications
3
82
2
Order By: Relevance
“…As a result, the production cells grew considerably faster than the 11 non-scaffolded pathway expressed to levels required to achieve comparable titers. In the 12 present study, the modular architecture was utilized for the glucaric acid pathway to shown to possess activity against myo-inositol-1-phosphate (Matsuhisa et al, 1995). We 17 have over-expressed the suhB gene in an attempt to improve glucaric acid productivity; 18 however, the titers have always decreased in response to suhB (data not shown).…”
Section: Discussion 19mentioning
confidence: 99%
“…As a result, the production cells grew considerably faster than the 11 non-scaffolded pathway expressed to levels required to achieve comparable titers. In the 12 present study, the modular architecture was utilized for the glucaric acid pathway to shown to possess activity against myo-inositol-1-phosphate (Matsuhisa et al, 1995). We 17 have over-expressed the suhB gene in an attempt to improve glucaric acid productivity; 18 however, the titers have always decreased in response to suhB (data not shown).…”
Section: Discussion 19mentioning
confidence: 99%
“…(Fig. 1a, boxed sequence) (Matsuhisa et al, 1995). We investigated whether the suhB Bc deletion mutant (herein DsuhB Bc ) has a growth defect.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism of action of SuhB Ec remains unclear. In vitro, purified SuhB Ec has IMPase activity (Matsuhisa et al, 1995). However, a SuhB Ec mutant protein D87N that lacks IMPase activity remains fully functional in complementing a defective suhB mutant (Chen & Roberts, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…coli has five Li ϩ -sensitive phosphatases as follows: CysQ (a PAPase), SuhB (an IMPase), Fbp (a FBPase I enzyme), GlpX (a FBPase II), and YggF (an uncharacterized protein) (see the Pfam data base). CysQ is a 3Ј-phosphoadenosine 5Ј-phosphatase involved in the cysteine biosynthesis pathway (25,26), whereas SuhB is an inositol monophosphatase (IMPase) that is also known as a suppressor of temperature-sensitive growth phenotypes in E. coli (27,28). Fbp is required for growth on gluconeogenic substrates and probably represents the main gluconeogenic FBPase (12).…”
mentioning
confidence: 99%